2024
DOI: 10.1007/s10142-024-01292-4
|View full text |Cite
|
Sign up to set email alerts
|

LINC00942 inhibits ferroptosis and induces the immunosuppression of regulatory T cells by recruiting IGF2BP3/SLC7A11 in hepatocellular carcinoma

Dong Jin,
Yongfeng Hui,
Di Liu
et al.

Abstract: Hepatocellular carcinoma (HCC) is a common malignant tumor with a high recurrence rate and a poor prognosis. Long intergenic nonprotein coding RNA 942 (LINC00942) is reported to be related to ferroptosis and the immune response in HCC and serves as an oncogene in various cancers. This research aimed to explore the contribution of LINC00942 in HCC progression. Functional assays were used to evaluate the functional role of LINC00942 in vitro and in vivo. Mechanistic assays were conducted to assess the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous outcomes might be triggered by some common confounders shared by HCC and IgD-CD27-AC. Jin et al explored that long intergenic nonprotein coding RNA 942 promotes HCC cell proliferation and converts naive CD4 T cells into inducible Treg (iTreg) cells by regulating solute carrier family 7 member 11, suggesting a protective role for naive CD4 + T cells in HCC pathogenesis [52]. Moreover, it has been found that the knockdown of Tubulin γ-1 (TUBG1) has been shown to inhibit the proliferation, invasion, and migration of HCC cells and TUBG1 expression was negatively correlated with CD4 + regulatory T-cell [53], which is in line with our MR results and supports a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous outcomes might be triggered by some common confounders shared by HCC and IgD-CD27-AC. Jin et al explored that long intergenic nonprotein coding RNA 942 promotes HCC cell proliferation and converts naive CD4 T cells into inducible Treg (iTreg) cells by regulating solute carrier family 7 member 11, suggesting a protective role for naive CD4 + T cells in HCC pathogenesis [52]. Moreover, it has been found that the knockdown of Tubulin γ-1 (TUBG1) has been shown to inhibit the proliferation, invasion, and migration of HCC cells and TUBG1 expression was negatively correlated with CD4 + regulatory T-cell [53], which is in line with our MR results and supports a causal relationship.…”
Section: Discussionmentioning
confidence: 99%